Harnessing the potential of sugarcane-based liquid byproducts—molasses and spentwash (vinasse) for enhanced soil health and environmental quality. A systematic review - Stephen, Gerison Saddick; Shitindi, Mawazo Jamson; Bura, Magdalena Deemay; Kahangwa, Caren Anatory; Nassary, Eliakira Kisetu (Frontiers in Agronomy, 2024)
Farming practices reliant solely on synthetic agrochemicals face unreliability in the current era marked by unpredictable climate changes and rapid soil health deterioration. Consequently, a shift towards sustainable approaches is imperative to ensure both food security and environmental quality. Molasses and vinasse, abundant organic liquid by-products from sugar processing and distillery industries respectively, have historically served as soil conditioners and biofertilizers. Despite their potential, their effectiveness as organic amendments remains relatively unknown globally. In response, we conducted a systematic literature review to unveil the benefits of molasses and vinasse as organic amendments. Our findings reveal that these by-products consist of both inorganic and organic compounds that enhance soil and aquatic ecosystem performance. These compounds include essential plant nutrients as mineral elements and organic matter, contributing to improved soil physico-chemical and biological properties. Notably, the application of molasses and vinasse in crop production has demonstrated superiority over chemical fertilizers, particularly when combined with other inorganic amendments. Molasses and vinasse have been reported to significantly increase yield in several crops including sugarcane (Saccharum officinarum, tomatoes (Solanum lycopersicum), soybean (Glycine max), maize (Zea mays) and rice (Oryza sativa). Strategic utilization of vinasse has the potential to enhance environmental quality by reducing soil heavy metal loads and mitigating negative impacts associated with synthetic fertilizers. However, it is crucial to note that irregular disposal or misuse of these by-products can result in detrimental effects on the environment and human health. To encourage sustainable utilization on a global scale, it is essential to establish appropriate dosages, raise awareness among farmers and stakeholders regarding judicious use, and develop effective methods for handling and application of molasses and vinasse. This approach ensures cost-effective and environmentally friendly organic amendments, fostering a harmonious balance between agricultural productivity and ecological well-being.